مؤسسات التأمين في الجزائر - الواقع والتحديات - دراسة تحليلية 2010/2020 - حمزة, يومبعي; ابراهيم, مهيش; يوسف, جديد (جامعة الوادي - University of Eloued, 2023)
" تهدف هذه الدراسة الى واقع مؤسسات التأمين في الجزائر وأهم التحديات التي تواجهها ، وذلك من خلال قياس أداء مؤسسات التأمين وتحديد تواجده في دعم ونمو الاقتصاد بفضل أربعة مداخل رئيسية متمثلة في معدل اختراق التأمين ومعدل الكثافة ، التعويضات المدفوعة ، استثمارات شركات التأمين ومساهمتها في توظيف المورد البشري . كما توصلت الدراسة إلى أن ضعف قطاع التأمين في الجزائر من الناحیة الفنية و المالیة أدى إلى تراجع مساهمته في الاقتصاد، وهو ما يستدعي ضرورة العمل على تطوير هذا القطاع بما ینعكس إيجابا على دعم النمو الاقتصادي. وذلك من خلال تعزیز ثقافة التأمين وفتح المجال لتوسع شركات التأمين أمام القطاع الخاص بما یزید من المنافسة في القطاع ومن ثم تحقيق تطور أكبر في الخدمات التأمينية المقدمة. أوصت الدراسة بضرورة تطوير مؤسسات التأمين وذلك بتوفير بيئة اقتصادية سليمة وقوية, تنظيم وتحديث القطاع ,ابتكار منتجات تتوافق مع الظروف الاقتصادية والاجتماعية من أجل تحسين الخدمات التأمينية. ""This study aims at the reality of insurance institutions in Algeria and the most important challenges they face, by measuring the performance of insurance institutions and determining its presence in the support and growth of the economy thanks to four main entrances represented in the rate of insurance penetration and the rate of density, compensation paid, investments of insurance companies and their contribution to the employment of human resource . The study also concluded that the weakness of the insurance sector in Algeria, technically and financially, led to a decline in its contribution to the economy, which necessitates the need to work on developing this sector in a way that reflects positively on supporting economic growth. This is done by promoting the culture of insurance and opening the way for insurance companies to expand in front of the private sector, which increases competition in the sector and then achieves a greater development in the insurance services provided . The study recommended the need to develop insurance institutions by providing a sound and strong economic environment, organizing and modernizing the sector, creating products that are compatible with economic and social conditions in order to improve insurance services "
Keywords: التأمين, معدل الاختراق, معدل الكثافة، تعويضات, توظيفات, مؤسسات التأمين الجزائري; Insurance, Penetration rate, Density rate, Indemnities, Employment, Algerian insurance sector .